Appendix 4.7: Marcos Diary Entry, 16 September 1971 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Marcos here talks about being stoic on the outside, but “irritable and sensitive” on the inside, though does not specify why. That the dinner described here had in attendance Ferdinand Marcos, Justice Fred Ruiz Castro, and Senator Jose Roy, Marcos’s partymate and president protempore of the Senate of the Philippines, meant that there were representatives of all branches of government during these early stages of priming the country for martial law.